2009
DOI: 10.1080/02652030903046690
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of patterns of food packaging usage in Portuguese homes

Abstract: This study aimed to permit further refinements in exposure assessments for migrants from food-contact materials by contributing to the characterization, at the household level, of the food packaging usage (amount and type) of Portuguese urban families. Packages from domestic use were collected from a sample of 105 consumers from 34 households over a 30 day period. Collected packages (more than 6 000 items) were characterized in the laboratory and data were used to estimate: (i) global packaging usage and food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
(5 reference statements)
2
7
0
Order By: Relevance
“…Most of the food items (56.7%) consumed by the Portuguese population were package foods. In general, plastic was the most frequently reported packaging material, which is also observed in other studies using data from British children, Netherlands retail and household consumption from some Portuguese regions (Poças et al, 2009(Poças et al, , 2010Bouma et al, 2003;Foster et al, 2010). Multilayer material and plastic were the materials with more significant differences between the tested population groups.…”
Section: Discussionsupporting
confidence: 80%
“…Most of the food items (56.7%) consumed by the Portuguese population were package foods. In general, plastic was the most frequently reported packaging material, which is also observed in other studies using data from British children, Netherlands retail and household consumption from some Portuguese regions (Poças et al, 2009(Poças et al, , 2010Bouma et al, 2003;Foster et al, 2010). Multilayer material and plastic were the materials with more significant differences between the tested population groups.…”
Section: Discussionsupporting
confidence: 80%
“…From recent surveys, it is clear that the ratio of surface area of food packaging materials to food mass is in many cases higher than 6 dm 2 /kg (VKM, 2009). In a study of the diet of a general population, performed in households in Portugal (Poças et al, 2009), the average ratio was found to be 11.7 dm 2 /kg overall, with a value of 7.2 dm 2 /kg specifically for cartons containing liquids. A UK survey found that the ratio for infants (less than 12 months old) was, on average, less than 6 dm 2 /kg (Foster et al, 2010), but this was said to be due to the large contribution of either breast milk or tap water used to reconstitute infant formula in this age group.…”
Section: The Ratio Of Food Mass To Contact Areamentioning
confidence: 99%
“…In a study of the diet of a general population, performed in households in Portugal (Poças et al, 2009), the average ratio was found to be 11.7 dm 2 /kg overall, with a value of 7.2 dm 2 /kg specifically for cartons containing liquids. A UK survey found that the ratio for infants (less than 12 months old) was, on average, less than 6 dm 2 /kg (Foster et al, 2010), but this was said to be due to the large contribution of either breast milk or tap water used to reconstitute infant formula in this age group.…”
Section: The Ratio Of Food Mass To Contact Areamentioning
confidence: 99%